Late‐Split Nitrogen Applications Increased Maize Plant Nitrogen Recovery but not Yield under Moderate to High Nitrogen Rates. (1st November 2017) - Mueller, Sarah M.; Camberato, James J.; Messina, Charlie; Shanahan, John; Zhang, Hao; Vyn, Tony J.
Abstract : Core Ideas: Late‐split N applications at V12 increased total N uptake and N recovery efficiency. Gains in N recovery with late‐split N came from increased post‐silking N uptake. Increased whole‐plant N accumulation by R6 did not result in increased grain yields. Grain yield was not sensitive to in‐season N timing in this single‐location study. Newer (2012, 2014) and older (1993, 1995) hybrids respond similarly to late‐split N. Theoretically, N losses are reduced by synchronizing fertilizer additions with plant uptake requirements. We investigated the impacts of supplemental, late‐season N applications on nitrogen fertilizer recovery efficiency (NRE), and N accumulation and partitioning in maize ( Zea mays L.) at silking (R1) and physiological maturity (R6). Also tested was whether modern hybrids responded differently to split‐N applications compared to hybrids released 20 yr ago. We compared 3 to 4 N rates ranging from 0 to 245 kg N ha −1 applied either in a single application at V3, or split with the last 45 kg N ha −1 delayed until V12, over 3 yr. Two newer hybrids (2012 and 2014) and two 1990 era hybrids (1991 and 1995) were compared at all N treatment combinations. Additional plant N accumulation following late‐split N applications was already apparent at R1, particularly in stems. Late‐split N application increased both whole‐plant R6 N accumulation and NRE through higher post‐silking N uptake. However, these benefits were rarely accompanied by increased grain yields. We found little evidence of differential hybrid responses to N rate or timing treatments. Principal component analysis revealed that the most consistent predictor of high post‐silking N uptake was lower N remobilization during grain‐fill; these had a strong inverse relationship. Therefore, gains from N management programs aiming to increase post‐silking N uptake are most likely in environments where whole‐plant N accumulation at R1 (and, consequently, potential N remobilization) is reduced. Further studies of late‐split N approaches are most warranted at lower total‐season N rates.